2022
DOI: 10.1002/hbm.25894
|View full text |Cite
|
Sign up to set email alerts
|

Connectomic assessment of injury burden and longitudinal structural network alterations in moderate‐to‐severe traumatic brain injury

Abstract: Traumatic brain injury (TBI) is a major public health problem. Caused by external mechanical forces, a major characteristic of TBI is the shearing of axons across the white matter, which causes structural connectivity disruptions between brain regions. This diffuse injury leads to cognitive deficits, frequently requiring rehabilitation. Heterogeneity is another characteristic of TBI as severity and cognitive sequelae of the disease have a wide variation across patients, posing a big challenge for treatment. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…While this paper is the first to apply graph matching to investigate the similarities of FCs between individuals, previous work has used graph matching to measure similarity between FC and SC and individuals' SCs. One such work in individuals with traumatic brain injury (TBI) used graph matching to capture SC network integrity after injury and in recovery; specifically they showed that individuals with TBI have more heterogeneity in their SCs than healthy controls, and this heterogeneity increases over time and is related to cognitive scores (Osmanlıŏlu et al, 2022 ). Graph matching has also been used in the past to map SC and FC to one another within individuals; that study found highest structure–function alignment in visual and somatomotor networks and lowest alignment in association regions (Osmanlioğlu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…While this paper is the first to apply graph matching to investigate the similarities of FCs between individuals, previous work has used graph matching to measure similarity between FC and SC and individuals' SCs. One such work in individuals with traumatic brain injury (TBI) used graph matching to capture SC network integrity after injury and in recovery; specifically they showed that individuals with TBI have more heterogeneity in their SCs than healthy controls, and this heterogeneity increases over time and is related to cognitive scores (Osmanlıŏlu et al, 2022 ). Graph matching has also been used in the past to map SC and FC to one another within individuals; that study found highest structure–function alignment in visual and somatomotor networks and lowest alignment in association regions (Osmanlioğlu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…While this paper is the first to apply graph matching to investigate the similarities of FCs between individuals, previous work has used graph matching to measure similarity between FC and SC and individuals' SCs. One such work in individuals with traumatic brain injury (TBI) used graph matching to capture SC network integrity after injury and in recovery; specifically they showed that individuals with TBI have more heterogeneity in their SCs than healthy controls, and this heterogeneity increases over time and is related to cognitive scores 65 . Graph matching has also been used in the past to map SC and FC to one another; that study found highest structure-function alignment in visual and somatomotor networks and lowest alignment in association regions 43 , which reflects our current results showing least inter-subject FC alignment for association and most for sensory-motor networks.…”
Section: Discussionmentioning
confidence: 99%